Quản trị công ty, cơ cấu vốn và hiệu quả kĩ thuật: Trường hợp các doanh nghiệp niêm yết tại Việt Nam - Vũ Thịnh , Trường; Võ Hồng , Đức; Lê Thị Thanh , Loan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
By adopting agency and stewardship theories, this study seeks to examine the effects of corporate governance and capital structure on technical efficiency of listed firms in the manufacturing/processing industry in Vietnam. Stochastic frontier analysis (SFA) and two-stage bootstrap data envelopment analysis (DEA) are applied to a dataset with 342 observations for the 2008–2014 period. The empirical results indicate that capital structure has a non-linear, inverted U-shaped relation with technical efficiency. Corporate governance mechanisms, which, in turn, have effects on technical efficiency, include duality, level of independent, non-executive directors, and number of meetings held. Finally, based on the findings the study draws a few implications for improving firms' performance.
Keywords: Technical efficiency; Listed firms; Corporate governance; Capital structure